Early warning mechanisms for online learning behaviors driven by educational big data - Xia, Xiaona, 1985-; Qi, Wanxue (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"The book aims to design and construct early warming mechanisms based on the dynamic temporal tracking technology for online learning behaviors, driven by educational big data. By studying a massive amount of learning behavior instances generated in various interactive learning environments worldwide, the book explores the continuous sequences of correlated learning behaviors and characteristics. From various angles, the authors have devised a series of early warning measures that could effectively solve multiple issues in learning behaviors driven by educational big data. Additionally, the book predicts patterns and identifies risks by analyzing the temporal sequences of the entire learning process. While presenting a range of theoretical achievements and technical solutions to improve and design new online learning mode, it also provides relevant technical ideas and methodologies for research on similar problems. The book will attract scholars and students working on learning analytics and educational big data worldwide"--
Introduction -- Multi-dimensional temporal fusion and risk prediction in interactive learning process -- Learning enthusiasm enabled dynamic early warning sequence model -- Early warning value propagation network for continuous learning behaviors -- Early warning pivot space model of multi temporal interactive learning process -- Early warning model design and decision application of unbalanced interactive learning behaviors -- Cost sensitivity analysis and adaptive prediction of unbalanced interactive learning behaviors -- Diagnostic analysis framework and early warning mechanism of forgettable learning behaviors -- Conclusion.
Keywords: Web-based instruction -- Evaluation; Web-based instruction -- Psychological aspects; Education -- Data processing; Big data; COMPUTERS / Information Technology; EDUCATION / Distance Education & Learning; EDUCATION / Educational Psychology